THE EFFECT OF JIGSAW TECHNIQUES ON THE READING COMPREHENSION ABILITY OF THE SECOND YEAR STUDENTS OF SMAN 2 PEKANBARU - Septami, Nadya; Azhar, Fadly; Gultom, Effendi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study aims to find out the effectiveness of Jigsaw Techniques on the reading comprehension ability of the second year students of SMAN 2 Pekanbaru, the technique that being used was Jigsaw IV. The researcher uses pre-experimental research design of one-group-pre-test-post-test. The researcher uses Cluster Random Sampling technique to determine the sample of the research. The population of this study is the second year students consisted of 5 science classes with total 172 students, from the population it was chosen that the sample is XI Science 1 class with 34 students. The research instrument is a reading test in the form of analytical exposition text using multiple-choice type of test and each question consists in four options (A, B, C, and D). The test consists of 5 analytical exposition passages based on the reading comprehension components with the total of 25 questions for both of pre-test and post-test. Before the test is administrated to the research sample, the researcher conducted a try-out of the test to non-experimental group to obtain the reliability and validity of the test using Heaton’s index of difficulty/Facility Value (FV) formula. The researcher uses application program such as Microsoft Excel and IBM-SPSS Statistics Version 23 to analyze the data. Based on the results, the T-Observation or T-Test is higher than T-Table (to > tt , to = 12.754, tt = 2.03452 (2.035)). The probability is in sig. 2 tailed with  = 5% (0.05) that it is displayed in T-Test table of sig.2 tailed = 0.000 with df = n-1 = 33. Then, t-observation result also shows that the student’s mean score of post-test (67.0588) is higher than the pre-test (53.0588). Furthermore, the Paired Sample Correlation shows 0.794 which is interpreted as strong. It can be concludes that there are good effects of Jigsaw IV technique and solved the second year students’ problem on reading comprehension especially towards students’ reading comprehension of SMAN 2 Pekanbaru. It is suggested that Jigsaw IV technique can be applied not only for junior high school level, undergraduate students level, EFL students level, and students in science class but also can be applied for second year of senior high school level.Keywords: Effect, Jigsaw IV Technique, Reading Comprehension, Ability, Senior High School, Second Year Students.